PENGARUH KUALITAS STRATEGI MEMBACA TERHADAP PRESTASI AKADEMIK - Suprihadi Suprihadi; Muh. Syafei (Jurnal Penelitian Humaniora, 2019)
The dual-role of the students of English Education Department Teacher Training and Education Faculty Muria Kudus University as both English language learners and language users gets them to be autonomous, effective, efficient, and strategic readers. The objective of this research is to investigate the relationship between quality of the reading strategy and academic achievement of the students. The subjects of this research were 104 students of EED UMK comprising of all semesters taken randomly. The instrument used was closed-ended questionnaire. The result of this research reveals that there is no relationship between quality of the reading strategy and academic achievement, meaning that the quality of reading strategy does not influence the academic achievement of the students. Implikasions and recommendations for the institution and for further research were proposed.